PENGARUH MINAT BELAJAR, DISIPLIN BELAJAR, GAYA BELAJAR, FASILITAS BELAJAR DAN PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA KELAS X FASE E PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 LEMBAH GUMANTI - Helviza, Feza; Stevani; Vivina Eprillison (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze: 1) The effect of Learning Interest on the Learning Achievement of Class X Phase E Students at SMA Negeri 1 Lembah Gumanti 2) The effect of Learning Discipline on the Learning Achievement of Class X Phase E Students at SMA Negeri 1 Lembah Gumanti 3) The effect of Learning Style on the Learning Achievement of Class X Phase E Students at SMA Negeri 1 Lembah Gumanti 4) The effect of Learning Facilities on the Learning Achievement of Class X Phase E Students at SMA Negeri 1 Lembah Gumanti 5) The effect of Parental Attention on the Learning Achievement of Class X Phase E Students at SMA Negeri 1 Lembah Gumanti 6) The combined effect of Learning Interest, Learning Discipline, Learning Style, Learning Facilities, and Parental Attention on the Learning Achievement in Economics for Class X Phase E Students at SMA Negeri 1 Lembah Gumanti. This type of research is quantitative. The population in this study is the students of class X Phase E at SMA Negeri 1 Lembah Gumanti, totaling 96 individuals. The sampling technique used is Total Sampling where the entire population is made into a sample, which amounts to 96 people. Data analysis is assisted by the SPSS program version 15. The results of this study indicate that: 1) There is a positive and significant influence of interest in learning on academic achievement with a coefficient value of the interest in learning variable (X1) of 0.253 and a tcalculated value of 1.617 > ttable of 1.66088 with a significant value of 0.109 <= 0.05. 2) There is a positive and significant influence of discipline in learning on academic achievement with a coefficient value of the discipline in learning variable of 0.514 and a tcalculated value of 3.3999 > ttable of 1.66088 with a significant value of 0.001 <= 0.05. 3) There is no significant influence of learning style on academic achievement with a coefficient value of the learning style variable of -0.316 and a tcalculated value of -1.892 > ttable of 1.66088 with a significant value of 0.062 >= 0.05. 4) There is no significant influence of learning facilities on learning achievement, with a coefficient value of the learning facilities variable being 0.083 and a tcalculated value of 774 ≤ ttable of 1.66088 with a significance value of 0.441 ≥ 0.05. 5) There is a positive and significant influence of parental attention on learning achievement, with a coefficient value of the parental attention variable being 0.409 and a tcalculated value of 3.632 > ttable of 1.66088 with a significance value of 0.000 ≤ 0.05.